Population genetic structure of the sea urchin Tripneustes gratilla from selected sites in Western Luzon and Eastern Philippines - Malay, Maria Celia D. (Animo Repository, 2000)
The genetic structure of the sea urchin Tripneustes gratilla was investigated for six wild populations in western Luzon and eastern Philippines and one batch of hatchery-reared sea urchins. Analysis of six polymorphic allozyme loci revealed low levels of genetic differentiation (Nei’s unbiased D = 0.0 – 0.014, overall FST =0.0122), implying extensive gene flow between populations. The batch of cultured T. gratilla showed no apparent genetic distinctness from wild populations. Genetic differentiation was slightly higher in one eastern population (Ticao, Masbate). Structuring was not associated with geographic distance, but might be a result of heterogeneous recruitment. Initial results suggest that intensively-fished T. gratilla populations in northwestern Luzon should be managed as a single unit, hence a region-wide fishery management scheme needs to be implemented. The establishment of a network of marine protected areas along the western coast of Luzon is also recommended